Ayahuasca: Between Cognition and Culture - Ismael Eduardo Apud Peláez (Antropologia Mèdica, 2020)
This book summarizes Ismael Apud's ethnographic research in the field of ayahuasca, conducted in Latin America and Catalonia over a period of 10 years. To analyze the variety of ayahuasca spiritual practices and beliefs, the author combines different approaches, including medical anthropology, cognitive science of religion, history of science, and religious studies. Ismael Apud is a psychologist and anthropologist from Uruguay, with a PhD in Anthropology at Universitat Rovira i Virgili.